Evaluation of Occupation Related Burnout among Nursing Professionals in Riyadh, Saudi Arabia – A Descriptive Cross Sectional Study - Alghamdi, Alya (Asian Journal of Pharmaceutics (AJP), 2024)
Background and Aim: The prevalence of burnout is increasing among healthcare professionals, particularly among nurses, due to their multiple roles in healthcare. There are limited studies assessing burnout among nurse providers in Saudi Arabia. Therefore, this study aimed to assess occupation-related burnout among nurse professionals in Riyadh, Saudi Arabia. Methods: A descriptive cross-sectional study was conducted to evaluate burnout among nurse providers. Nurse providers working in a tertiary hospital in Riyadh were recruited for the study. Structured, pre-validated questionnaires were used to assess burnout among nurse professionals. Data analysis was performed using statistical software package, version 26 (SPSS Inc., Armonk, New York, United States). Results: A total of 120 nurses responded to the study (82.5% females) and were included in the final analysis. Among the respondents, 74% were aged over 30 years, 67.5% were single, 47.5% of the nurses had 2–5 years of experience, while 40% had over 5 years of work experience. The findings revealed that 26.7% of the nurses never felt emotionally exhausted because of their work, while 11.7% felt that way every day. In addition, 27.5% of the nurses agreed that working with people all day is stressful. Furthermore, 19.2% felt that their work was breaking them down. Of the nurses in this survey, 13.3% reported feeling exhausted as soon as they saw a new workday ahead of them, compared to 24.2% who said they never felt tired at all. Moreover, 13.3% of the nurses revealed that they easily understood the actions of their patients every day, while 25% never understood it easily. In addition, 15.8% of the nurses agreed that they successfully dealt with other people’s problems every day, while 16.7% agreed that they dealt with them several times a month. Conclusion: Nurses in the current study exhibited burnout in various aspects of their work in terms of emotional exhaustion, depersonalization, and personal achievement. In today’s society, the concept of occupational burnout is increasing due to multiple factors. Therefore, there is a need to raise understanding and awareness of management techniques for burnout among health-care professionals, particularly nurses.